MODERN TRENDS TO MANAGEMENT COMPETITIVENESS AND QUALITY ON THE BASIS OF TQM - Stankovska , I. M. (The actual problems of regional economy development, 2018)
Іn the article the tendencies of the development of the concept of TQM are studied, further development of the issue related to the implementation of the concept of TQM in energy companies. Established that TQM is a dynamic concept that is constantly evolving, including new modern methods and approaches for effective business conduct, and is the key to its development and competitiveness. TQM approaches are flexible, this philosophy of management, which defines the basic concepts of the enterprise, leaves the freedom to choose the ways of their implementation. Using the benchmarking method, the Consumer Power Supply Quality Index (SAIDI) has been considered. In order to improve production processes, it is proposed to apply the main approaches of the TPS system, which will ensure the effective implementation of the concept of TQM in energy market enterprises.